27.1k views
2 votes
What is the solution of 2d=a-b/b-c when you solve for a

User ClicheName
by
4.7k points

1 Answer

2 votes

Answer:

2d(b-c)+b=a

Explanation:

First you start off with the equation given

2d=(a-b)/(b-c)

Second, you want to start getting A by its self so that means you have to multiply both sides by (b-c) to get (a-b) by its self. (underlined portion cancles out)

2d(b-c)=((a-b)/(b-c)) (b-c) ----> 2d(b-c)=a-b

Finally, you want to add b to both sides to get a completely by it's self. (underlined portion cancles out)

2d(b-c)+b=a-b+b -----> 2d(b-c)+b=a

User Ddelizia
by
5.3k points